Automated method for the estimation of serum protein-bound iodine following alkaline incineration - Welshman, S. G. (1966)
A method is described for the estimation of serum protein-bound iodine using alkaline incineration and an automated technique for the estimation of iodine in the ash. Pretreatment of the serum with an anion exchange resin avoids the need for precipitation and washing of the protein. The method is accurate, reproducible, and simple to perform.